EVALUATION OF IMPROVED POLY VOLTINE XBIVOLTINE HYBRIDS OF SILKWORM BOMBYX MORI L. UNDER LARGESCALE IN-HOUSE TESTING - ., DAYANANDA; GOPINATH, O.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
In the present study, an attempt has been made to assess the in-house large scale performance of new póly voltine X bivoltine hybrids of silkworm Bombyx mori L., A GL3 X CSR2 and A GL5 x CSR2 under simulated farmers conditions for their rearing and reeling characters in comparison with the existing commercial hybrid, PM x CSR2. All the hybrids were reared thrice in four replications at the rate of 50 difls/replication. Data was collected for twelve qualitative and quantitative economic parameters and analyzed statistically. The results indicated that, the new hybrids studied have excelled in their performance for most of the traits studied over the existing commercial hybrid. PM X CSR2 and proved promising for commercial exploitation. Among the new hybrids tested AGL5 X CSR2 recorded higher survival (85.25%), cocoon yield (72.055 kg/ 50000 eggs) and fetched higher cocoon rate (Rs. 138.00) compared to the control.